2002
DOI: 10.1097/00001665-200209000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial Traumas

Abstract: Craniofacial traumas often involve the orbital region. This report describes an unusual case of penetration of an object into the left upper oral vestibule up to the left medial-upper orbital wall. The object was an indicator switch. A multidisciplinary approach was necessary to make a correct diagnosis and to apply the best surgical treatment. The object was surgically removed, and rigid internal fixation was used to reconstruct the inferior and medial orbital walls. The aesthetic and functional results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In addition, limited contact plates can induce formation of a thin callus on the cortex surface, which is of significance in the treatment of panfacial fractures in elderly patients and worthy of further investigation. Importantly, distal and proximal tissues of the fractured bone must be healthy so as to provide adequate mechanical support and blood supply, and to avoid plate rupture caused by excessive distortion stress (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, limited contact plates can induce formation of a thin callus on the cortex surface, which is of significance in the treatment of panfacial fractures in elderly patients and worthy of further investigation. Importantly, distal and proximal tissues of the fractured bone must be healthy so as to provide adequate mechanical support and blood supply, and to avoid plate rupture caused by excessive distortion stress (23).…”
Section: Discussionmentioning
confidence: 99%
“…Examination of the 68 cases in this study revealed that internal rigid fixation cannot completely substitute for short‐term intermaxillary traction. Because the causes of fractured malocclusion can be complex (22, 23), including variable type of fracture, degree of dislocation of the bone pieces and degree of disorganization of the postoperative stomatognathic system, a combined approach of rigid internal fixation and intermaxillary traction is beneficial for restoring stomatognathic function and healing of broken ends. For example, fracture of the zygomatic complex can result in limited ability to open the mouth because of obstruction due to dislocation of the zygoma and zygomatic arch from the coracoid process of the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates the necessity of dentist in knowing the existence of anatomical structure and its characteristics, which may influence the conduct of treatment and avoid complications trans- and postsurgically, as observed in first case, with presence of painful symptoms and lip paresthesia. In addition, knowledge of this region may reduce the risk of damage to neurovascular supply, as in cases of traumas in maxillofacial region, such as Le Fort I fractures, which involves the separation of maxilla with palatine region, and Le Fort II fractures, which occurs through the nasal bones and orbital rim [ 12 ].…”
Section: Discussionmentioning
confidence: 99%